Robotic-Based Bottom Vehicle Inspection in Indonesian - Wibowo, Helmi; Hakim, M. Iman Nur (RSF Conference Series: Engineering and Technology, 2022)
In Motor Vehicle Testing, Bottom Vehicle Inspection is still done manually by means of the inspector entering the test box to see the Bottom Vehicle to ensure that the Bottom Vehicle is in good condition. Weaknesses of Manual Bottom Vehicle Inspection, making vehicle owners unable to see the condition of the Bottom Vehicle directly; if there is a problem at the Bottom of the vehicle, the vehicle inspector instructs the vehicle owner to go down under the test so that it takes up much time and there is a long queue. However, with current technological developments, it is possible for vehicle owners and vehicle inspectors to directly see the condition under the vehicle so as to create transparent public services by means of a robotic-based Bottom vehicle. This research aims to create a transparent public service between the vehicle inspector and the vehicle owner. This research method makes designs and builds Robot Bottom vehicles controlled by Arduino Nano and Raspberry. Arduino Nano is equipped with a stick to control the movement of the robot's wheel and robot arm; Raspberry is equipped with a camera to display the condition of the Bottom vehicle components and communication between systems using local area networks. The results showed that the Bottom vehicle could be seen directly and clearly so that if there is damage to the Bottom vehicle component, the vehicle owner can know firsthand the condition of the Bottom of the vehicle.